Whole-genome resequencing reveals new mutations in candidate genes for Beichuan-white goat prolificacya - Aimin Zhou; Yi Ding; Xiaohui Zhang; Yugang Zhou; Yadong Liu; Tingjian Li; Long Xiao (Animal Biotechnology, 2024)
In this study, we evaluated the copy number variation in the genomes of two groups of Beichuan-white goat populations with large differences in litter size by FST method, and identified 1739 genes and 485 missense mutations in the genes subject to positive selection. Through functional enrichment, ITGAV, LRP4, CDH23, TPRN, RYR2 and CELSR1 genes, involved in embryonic morphogenesis, were essential for litter size trait, which received intensive attention. In addition, some mutation sites of these genes have been proposed (ITGAV: c.38C > T; TPRN: c.133A > T, c.1192A > G, c.1250A > C; CELSR1: c.7640T > C), whose allele frequencies were significantly changed in the high fecundity goat group. Besides, we found that new mutations at these sites altered the hydrophilicity and 3D structure of the protein. Candidate genes related to litter size in this study and their missense mutation sites were identified. These candidate genes are helpful to understand the genetic mechanism of fecundity in Beichuan white goat, and have important significance for future goat breeding.